The Effect of Bargaining Power Determinants on Pharmaceutical Prices - Sebastian Linde; Brandon Norton; Ralph Siebert (Center for Economic Studies and ifo Institute (CESifo), 2019)
This paper provides insights into the determinants of bargaining power and how they affect drug prices. Our data show that drug prices vary across buyers and time periods. We estimate a structural bargaining model where drug suppliers and buyers engage in bilateral bargaining over drug prices. Our estimation results show that drug buyers hold, on average, 55% of the bargaining power. We also find that bargaining power can imply a range of drug prices. Differences in bargaining power explains large price heterogeneities across buyers, drug classes, and time periods. Additionally, of the drug price variation that is explained by bargaining power, differences across buyers rather than changes over time are more important. We examine buyer and seller characteristics that determine bargaining power and evaluate how changes in these bargaining power determinants affect bargaining power and prices. We find that transaction-specific determinants (such as transaction volume) and business relationships between buyers and sellers (such as buyer's loyalty and multiple drug purchases from the same seller) exert the strongest effects on improving buyer bargaining power and reducing drug prices. For example, an 10% increase in transaction volume, buyer's loyalty, and multiple drug purchases strengthens buyer's bargaining power and results in a drug price reduction of 12%.
Keywords: L10; 330; bargaining power; determinants of bargaining power; drug prices; drug price variation; business relationship between buyers and sellers